(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The aim of this paper is to bring generalized fixed point theorems via the interesting simulation functions in the context of interpolative metric spaces. The notion of interpolative metric space is introduced by KarapinarEK0, very recently. This new metric structure is a concrete generalization of the usual metric space which is indicated by examples.